Evaluation of the physical fitness of referees in Iceland : a comparison between football and handball referees - Jón Reynir Reynisson 1992-; Stefán Freyr Michaelsson 1988- (2018)
Professional football referees need a standardized physical testing system that can be administered regularly to maintain quality assurance in game play decision making. A quantitative study for officiating upper league referee’s physical capabilities was performed during the school year of 2017/2018 at Reykjavik University in order to examine the physical capabilities of referees in Iceland‘s top division football, all of whom are registered officials through the football association of Iceland, KSÍ (Knattspyrnusamband Íslands). In order to achieve this, we tested football referees from KSÍ in two physical agility tests, T-test and the Yo-yo Intermittent Recovery level II test (Yo-yo II, Yo-yo IR II). We also compared the referees to semiprofessional football players, which the referees of Iceland would govern during matches. A comparison to other upper level referees in team handball, HSÍ (Handboltasamband Íslands), a sport popular in Europe, was also conducted to see if and what the difference in capabilities is between professions. The results showed that both groups of referees were not as efficient as the players in all regards. The KSÍ referees did better than the HSÍ referees in the T-test with mean time of 10.07 ± 0.19 seconds for the KSÍ referees compared with 10.16 ± 0.15 seconds for the HSÍ referees. In contrast, the HSÍ referees did better in the Yo-yo II test, with mean distance of 420 ± 52 meters for the HSÍ referees compared with 364 ± 34 meters for the KSÍ referees. These results show that the younger athletes are in better shape than the older referees which is in accordance with other studies. Furthermore, the study shows that although the KSÍ referees were measured during their off-season training they did better than the HSÍ referees in their mid-season training in one of the two tests. Therefore, it may be concluded that the KSÍ referees are in overall better shape than the HSÍ referees. This needs to be confirmed with a larger cohort and comparing timing as of beginning, mid-term and end ...